(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
Leprosy is a chronic infectious disease with low pathogenicity caused by bacillus Mycobacterium Leprae, symptoms of this disease manifest in 20 years and it is not highly infectious as one thought (1). It is transmitted through droplets, from the nose and mouth during close and frequent contacts with untreated cases (2). It is claimed that infectious patient can be rendered non –infectious by treatment with Dapson for about 90 days or with Rifampicine for 3 weeks, so it is a curable disease and treatment provided in early stage prevents disability (3)(4). In many states of India leprosy patients continue to be discriminated against and subjected to worst kinds of cruelty by society , even several state’s laws have provisions that prohibit them from contesting elections, obtaining driving license, traveling in trains and even allowing the disease a valid ground for divorce.